Interferon beta-1b is effective in relapsing-remitting multiple sclerosis. II. MRI analysis results of a multicenter, randomized, double-blind, placebo-controlled trial. UBC MS/MRI Study Group and the IFNB Multiple Sclerosis Study Group. - Paty, D; Li, D (1993)
We performed yearly MRI analyses on 327 of the total 372 patients in a multicenter, randomized, double-blind, placebo-controlled trial of interferon beta-1b (IFNB). Clinical results are presented in the preceding companion paper. Baseline MRI characteristics were the same in all treatment groups. Fifty-two patients at one center formed a cohort for frequent MRIs (one every 6 weeks) for analysis of disease activity. The MRI results support the clinical results in showing a significant reduction in disease activity as measured by numbers of active scans (median 80% reduction, p = 0.0082) and appearance of new lesions. In addition, there was an equally significant reduction in MRI-detected burden of disease in the treatment as compared with placebo groups (mean group difference of 23%, p = 0.001). These results demonstrate that IFNB has made a significant impact on the natural history of MS in these patients.